The Legal Consolidation of Investment Right of Individuals Protection Measures in Shared Construction - E. B. Makushina (Теоретическая и прикладная юриспруденция)
The article is dedicated to analysis of the existing legal consolidation of investment right of individuals protection measures in shared construction. The author notes following disadvantages of the legal consolidation in escrow invoicing: the lack of indexing of investors’ money in the account; the lack of partial disclosure with the purpose of avoiding bankruptcy. The article shows the necessity of legal confirmation of investor control over the developer’s activities during the investment project implementation and proposes measures to enhance the protective mechanisms and investment risks reduction aimed at stimulating the citizens’ investment in construction.